Entrepreneurship, Innovation Ecosystems, and Post-Pandemic Economic Recovery Strategies - Omar Khaled Najjar Al Fatih (Journal of Nusantara Economy, 2025)
The post-pandemic period has fundamentally reshaped the global economic landscape, compelling governments, businesses, and local communities to develop more adaptive and innovation-oriented recovery strategies. Within this context, entrepreneurship and innovation ecosystems have emerged as critical drivers of economic resilience, business sustainability, and inclusive development. This study aims to analyze the interrelationship between entrepreneurial activities, innovation ecosystems, and post-pandemic economic recovery strategies, while identifying the institutional, technological, and collaborative factors that strengthen sustainable economic revitalization. The research employs a qualitative field research design, collecting primary data through semi-structured interviews, direct observations, and focus group discussions involving entrepreneurs, business incubator managers, government officials, financial institutions, and innovation ecosystem stakeholders. The data are analyzed using thematic analysis through data reduction, categorization, interpretation, and triangulation to ensure the credibility and trustworthiness of the findings. The results demonstrate that successful post-pandemic economic recovery depends not only on entrepreneurial capabilities but also on the maturity of innovation ecosystems characterized by effective collaboration among government, universities, industry, financial institutions, and digital technology providers. The findings further reveal that digital transformation, access to entrepreneurial financing, policy support, innovation-oriented business networks, and institutional capacity building significantly enhance business adaptability, accelerate innovation diffusion, and improve the resilience of micro, small, and medium-sized enterprises. Nevertheless, disparities in digital infrastructure, limited innovation capabilities, and uneven stakeholder coordination remain major obstacles to achieving sustainable recovery. This study contributes to the entrepreneurship and innovation literature by proposing an integrated recovery framework that combines entrepreneurial resilience, collaborative innovation ecosystems, and adaptive governance as complementary pillars for sustainable post-pandemic economic development. The findings also provide practical policy implications for strengthening innovation-driven entrepreneurship and designing more resilient, inclusive, and long-term economic recovery strategies.